PENINGKATAN HASIL BELAJAR MATEMATIKA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE NHT (Number Heads Together) - Hironimus Halim; Ryan Nizar Zulfikar; Nur R Adawiyah Mahmud (Program Studi Pendidikan Matematika, Universitas Muhammadiyah Kupang, 2021)
The objective of this qualitati veresearchist of indout the improvement of the students' math learning resultsusing NHT cooperative learning model (Numbered Heads Together). The data sources of this case study were secondary and primary data. (1) The primary data wereobtained from the information at the research site and (2) the secondary datawerecontainedof the attachments of the scientific journals review. The data were analyzedthrough data reduction, presentation, andconclusions or verification.This studywas about the improvement results of mathematics learning usingNHT cooperative learning model (Numbered Heads Together) in the tenth-grade students of SMK Muhammadiyah Kupangon matrix materials.The study showed that NHTcooperative learning model(Numbered Heads Together) could improve the math learning results of tenth-grade students ofSMK Muhamtsmadiyah Kupangon matrix materials.